2011
DOI: 10.1039/c1nr10172b
|View full text |Cite
|
Sign up to set email alerts
|

Differential nano-bio interactions and toxicity effects of pristine versus functionalized graphene

Abstract: We report the effect of carboxyl functionalization of graphene in pacifying its strong hydrophobic interaction with cells and associated toxic effects. Pristine graphene was found to accumulate on the cell membrane causing high oxidative stress leading to apoptosis, whereas carboxyl functionalized hydrophilic graphene was internalized by the cells without causing any toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
303
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(317 citation statements)
references
References 26 publications
10
303
2
2
Order By: Relevance
“…[ 69,70 ] While pristine carbon based materials tend to accumulate in physiological solution due to electrostatic interactions and nonspecifi c bindings to proteins, [ 71 ] surface-modifi ed graphene-like materials are often deemed to be less toxic. [ 70,72 ] Our results are consistent with these observations. These results demonstrate that the functionalization of coronene and TRGO with D -phenylalanine NDIs considerably improves the in vitro biocompatibility of the pristine PCSs presented in this work.…”
Section: Advsupporting
confidence: 83%
“…[ 69,70 ] While pristine carbon based materials tend to accumulate in physiological solution due to electrostatic interactions and nonspecifi c bindings to proteins, [ 71 ] surface-modifi ed graphene-like materials are often deemed to be less toxic. [ 70,72 ] Our results are consistent with these observations. These results demonstrate that the functionalization of coronene and TRGO with D -phenylalanine NDIs considerably improves the in vitro biocompatibility of the pristine PCSs presented in this work.…”
Section: Advsupporting
confidence: 83%
“…The presence of GBMs in the intracellular compartments has been observed among others by Sasidharan et al thanks to confocal microscopy 28 and Huang and co-workers via surfaceenhanced Raman spectroscopy 29 . However, the underlying mechanisms of cellular internalization of GBMs remain enigmatic and several pathways have been proposed.…”
Section: What Can Gbms Offer As Gene Delivery Platforms?mentioning
confidence: 92%
“…Some references revealed that hydrophilic GO is able to penetrate cell membranes, resulting in cytoplasmatic, perinuclear and nuclear accumulation [118][119][120]; while this behavior of GO can be inhibited by chemical or physical functionalization with polymers [120]. Furthermore, GO increases the surface hydrophilicity of the biocomposites, leading to improved biocompatibility [121].…”
Section: Biological Property Of Go-based Materialsmentioning
confidence: 99%